Normalisasi Hubungan Uni Emirat Arab dengan Israel - Wicaksono, Raden Mas Try Ananto Djoko (Indonesia Center for Middle East Studies, 2020)
The United Arab Emirates (UAE) and Israel have signed a normalization agreement called Abraham Accord on September 15, 2020. This agreement indicates that previously both countries had a reasonably good relationship and a series of cooperation. This study aims to see the UAE's interests toward Israel and how other Muslim countries respond to the agreement, which will impact their solidarity for Palestine's independence. In this research, the writer uses realism perspective, which includes the concept of national interest, the theory of balance of power, and the concept of normalization. The results showed that the UAE has an interest in expanding cooperation with Israel in various fields, especially in the political, economic, and security. The UAE made this policy because they feel threatened by Iran and because of the COVID-19 pandemic. This policy received positive response from Egypt, Jordan, Bahrain, and Sudan; and negative feedbacks from Oman, Iran, Turkey, and Qatar. Especially for Palestine itself, this agreement is a severe blow to the country's sovereignty struggle.